Novel lineage of a green alga and Acremonium stroudii (Ascomycota) sp. nov. reported from Ascension Island. (21st September 2015) - Fletcher, K.I.G.; Sim, J.; Williams, N.; Weber, N.; Küpper, F.C.; van West, P.
Abstract : Environmental specimens lining seawater blowholes of Whale Point, Ascension Island in the South Atlantic Ocean were collected (August 2012) and investigated by morphological and molecular techniques. Reported here, Acremonium stroudii (Ascomycota) sp. nov., a filamentous conidia-forming fungus, was the only fungus isolated from the samples collected. Molecular analysis of the material also indicates the presence of a novel species of green algae being present, however, isolation of this alga has not been possible. Instead it appears that this specimen, which belongs to a novel lineage within the Ulvales, sister to the Dilabifilum species, encourages fungal growth in culture and has been shown to form a symbiotic relationship on low nutrition agar plates, supported by investigation through electron microscopy. As no holotype of this species could be isolated in an axenic culture it was not suitable at this point to try to define this alga, especially as no established genus could be attributed. We recommend trying to further sample areas of Ascension Island looking for other members of this green algal lineage, both investigating free-living green algae and those which are found as lichenized photobionts.